Reproducibility of academic preclinical translational research: lessons from the development of Hedgehog pathway inhibitors to treat cancer. Issue 8 (1st August 2018) - Curran, Tom
Abstract : Academic translational research is growing at a great pace at a time in which questions have been raised about the reproducibility of preclinical findings. The development of Hedgehog (HH) pathway inhibitors for the treatment of cancer over the past two decades offers a case study for understanding the root causes of failure to predict clinical outcomes arising from academic preclinical translational research. Although such inhibitors were once hoped to be efficacious in up to 25% of human cancer, clinical studies showed responses only in basal cell carcinoma and the HH subtype of medulloblastoma. Close examination of the published studies reveals limitations in the models used, lack of quantitative standards, utilization of high drug concentrations associated with non-specific toxicities and improper use of cell line and mouse models. In part, these issues arise from scientific complexity, for example, the failure of tumour cell lines to maintain HH pathway activity in vitro, but a greater contributing factor appears to be the influence of unconscious bias. There was a strong expectation that HH pathway inhibitors would make a profound impact on human cancer and experiments were designed with this assumption in mind.